Design and Preparation of Polymer Resin‐Supported Proline Catalyst with Industrial Application Potential. Issue 9 (21st June 2016) - Xu , Mr. Lin; Huang , Mr. Jiejun; Zhang, Ming; Yu , Lei; Fan, Yining
Abstract: A polymer resin‐supported proline catalyst was developed. The material might serve as an eco‐friendly recoverable organocatalyst with industrial application potential. Its catalytic activity in acetone condensation was tested. Catalyst prepared under optimized conditions showed good performances, giving mesityl oxide (MO), diacetone alcohol (DAA) and isophorone (IP) in up to 87.7 % total selectivity, while the catalyst could be recovered with less than 5 % mass lost and could be reused for at least seven times without deactivation. Being able to convert market‐excess acetone into useful bulk fine chemicals, the catalyst is of significant industrial value. Abstract : Polymer resin‐supported proline catalyst was designed and prepared. The material showed excellent catalytic activities in acetone condensation, giving the useful products mesityl oxide (MO), diacetone alcohol (DAA) and isophorone (IP) in up to 87.7 % total selectivity, while the catalyst was recovered with less than 5 % of mass lost and could be reused for at least seven times without deactivation.